Does food disgust has a relationship with Orthorexia Nervosa? Correlation with gender and body mass index: Food Disgust and the Relationship to Orthorexia Nervosa - Arusoglu, Gülcan (Progress in Nutrition, 2020)
Objective: This study was conducted to determine the association of the predisposition to food disgust and orthorexic tendencies to gender, BMI and some variables. It is the first study to assess food disgust, disgust propensity and sensitivity and its relationship to orthorectic tendencies in Turkish sample.Method: The study was conducted on a total of 300 young individuals, consisting of 199 males and 101 females. The Food Disgust Scale (FDS), Orthorexia Nervosa (ON) (ORTO-11) Scale, Disgust Propensity and Sensitivity Scale- Revised (DPSS-R) and a personal information form were administered.Result: The average age of the individuals was 24.28±6.60 year. The mean BMI of men (23.88 ± 3.31 kg/m2) was significantly higher than women (21.64 ± 3.50 kg/m2) (p